Some genetic effects of Nerium oleander flower extract on male Mus musculus rats (Journal of the College of Basic Education, 2022)
The present study was designd to shed some light on the genetic effects of the flower extract of Nerium oleander .The effects of the extract on the mutagenic action of the drug Mytomicine-c (MM-C) were also investigated invivo using albino mous (Mus musculus).The genetic tests included mitotic index of bone marrow, thymic, and spleenic cells,chromosomal aberrations, micronucleus formation in bone marrow cells, and sperm-head abnormality assay.Three doses of extract were tested, they were(11, 22, 33mg/kg).The administration of extract when were given after the drug.Therefore, from the genetic point of view, the extract can be considered as direct desmutagenes in the first place and as biodesmutagenes in the seconed place.